Pendekatan-Pendekatan Dalam Studi Demokrasi Di Asia Tenggara Dan Relevansinya Untuk Indonesia - Abubakar E. Hara (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
Democratization in Southeast Asian countries is often perceived as transforming the countries into a kind of Western liberal democracy. By using Indonesian case, this paper, however, shows that this perception does not reflect current complexities in political arena. The transition to democracy in Indonesia has both the elements of modern and traditional political cultures and institutions. The paper suggests that democratization is better seen from the process of adaptation and hybridization of the modenrn and traditional aspects of Indonesian politics.